2015
DOI: 10.1136/bmjopen-2014-006947
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Polish version of the Knee injury and Osteoarthritis Outcome Score (KOOS) in patients with osteoarthritis undergoing total knee replacement

Abstract: ObjectiveTo test the clinimetric properties and to evaluate the internal consistency, validity and reliability of the Polish version of the Knee injury and Osteoarthritis Outcome Score (KOOS) in older patients with end-stage knee osteoarthritis undergoing total knee replacement (TKR).Design and settingA prospective cohort study performed at the university hospital and the outpatient clinic.MethodsThe patients were asked to complete the KOOS questionnaire and the Short Form 36 Health Survey. We evaluated floor/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 36 publications
8
52
1
Order By: Relevance
“…TKR is a procedure with steady increase in the clinical activity and research and thus a reliable and detailed understanding of the clinical outcome is need. To our knowledge, only two previous studies have validated the KOOS specifically in a cohort of elderly patients who have undergone TKR . Overall, the results of the present study were comparable to those studies, despite the fact that one of those study had smaller sample size, and to the original KOOS …”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…TKR is a procedure with steady increase in the clinical activity and research and thus a reliable and detailed understanding of the clinical outcome is need. To our knowledge, only two previous studies have validated the KOOS specifically in a cohort of elderly patients who have undergone TKR . Overall, the results of the present study were comparable to those studies, despite the fact that one of those study had smaller sample size, and to the original KOOS …”
Section: Discussionsupporting
confidence: 80%
“…There was high test–retest reproducibility for all KOOS subscales, with ICCs ranging from 0.76 to 0.91, which revealed satisfactory stability and reproducibility of the KOOS over time in our patients. The ICCs values were comparable to those observed in previous studies performed in patients who underwent TKR . The Sports/Recreational subscale had the lowest ICC (0.76) which suggested that the questions about these activities were relevant in the patients underwent TKR.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[5678912141516] This high Cronbach's alpha indicates that IKOOS is homogeneous and internally consistent. Only the symptom subscale in Iranian,[17] Dutch,[13] Spanish,[11] and Greek[10] version was lower than 0.7.…”
Section: Discussionmentioning
confidence: 99%